2022
DOI: 10.1186/s12911-021-01742-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing machine learning algorithms for predicting COVID-19 mortality

Abstract: Background The coronavirus disease (COVID-19) hospitalized patients are always at risk of death. Machine learning (ML) algorithms can be used as a potential solution for predicting mortality in COVID-19 hospitalized patients. So, our study aimed to compare several ML algorithms to predict the COVID-19 mortality using the patient’s data at the first time of admission and choose the best performing algorithm as a predictive tool for decision-making. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 45 publications
(55 reference statements)
3
48
2
1
Order By: Relevance
“…In general, our results showed that random forest showed regular performance compared to SVM and DF. In other studies, RF has shown the best performance in a study with smaller data volumes than those obtained in our research [21].…”
Section: Discussionsupporting
confidence: 52%
“…In general, our results showed that random forest showed regular performance compared to SVM and DF. In other studies, RF has shown the best performance in a study with smaller data volumes than those obtained in our research [21].…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Khan et al [22] examined three comorbidities (cardiac problems, diabetes, hypertension) as significant features. However, Pezoulas et al [24] found that some lab tests are a significant attribute in predicting mortality, while Moulaei et al [25] discovered that shortness of breath and extra oxygen therapy are among the top features to predict mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study was made by Moulaei et al [25] to compare the performance of different ML techniques to predict mortality using data at the time of admission to hospital. The dataset contained the patients' clinical, demographic, and laboratory results.…”
Section: Ai-based Studies To Predict Early Mortality In Covid-19 Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods of machine learning is interpretable decision trees, which are considered classification techniques in data mining [ 11 ]. One of the most popular usages of decision trees is to display the results as a simple decision tree algorithm that is easy to interpret for most researchers.…”
Section: Introductionmentioning
confidence: 99%